Assessment of the robustness of volumetric-modulated arc therapy for lung radiotherapy - Edmunds, K (The British Institute of Radiology., 2013)
Volumetric-modulated arc therapy (VMAT) is increasingly popular as a treatment method in radiotherapy owing to the speed with which treatments can be delivered. However, there has been little investigation into the effect of increased modulation in lung plans with regard to interfraction organ motion. This is most likely to occur where the planning target volume (PTV) lies within areas of low density. This paper aims to investigate the effect of modulation on the dose distribution using simulated patient movement and to propose a method that is less susceptible to such movement. Simulated interfraction motion is achieved by moving the plan isocentre in steps of 0.5 cm and 1.0 cm in six directions for five clinical VMAT patients. The proposed planning method involves optimisation using a density override of 1 g cm(−3), within the PTV in lung, to reduce segment boosting in the periphery of the PTV. This investigation shows that modulation can result in an increase in the maximum dose of >25%, an increase in PTV near-maximum dose of 17% and a reduction in near-minimum dose by 46%. Unacceptable organ at risk (OAR) doses are also seen. The proposed method reduces modulation, resulting in a maximum dose increase of 10%. Although safeguards are in place to prevent the increased dose to OARs from patient movement, there is nothing to prevent the increased dose as a result of modulation in lung. A simple planning method is proposed to safeguard against this effect. Investigation suggests that, where modulation exists in a plan, this method reduces it and is clinically viable.